Towards precision medicine: CCL2, another brick in the wall?. Issue 3 (7th March 2019) - Charpidou, Andriani; Kotteas, Elias; Gaga, Mina
The introduction of targeted treatment in lung cancer has substantially changed the outcome of disease and the lives of lung cancer patients. Having biomarkers that can identify the right candidates and that predict the response to a specific treatment is very important and currently, research focuses on the identification of reliable molecular markers. In this issue of the European Respiratory Journal, Lu et al. [1] provide insight into the mechanisms of action of a new medication, anlotinib, and propose a new, predictive biomarker, the C-C motif ligand 2 (CCL2). Research for predictive biomarkers that are crucial to decisions for targeted treatments is very important; the data should be validated in large studies http://ow.ly/mzis30neEA6